(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the duration of hospitalization and clinical outcome in children infected with methicilline-sensitive staphylococcus aureus and methicillin-resistant Staphylococcus aureus.(MRSA and MSSA) Study Design: comparative cross sectional Place and Duration of Study: This Study was carried out at the Paediatrics Department, Nishtar hospital Multan from 14.01.2012 to 13.07.2012 Materials and Methods: Children meeting the inclusion criteria were selected. Clinical samples were collected before starting antibiotics and sent to microbiology lab for culture. Colony morphology, gram straining and production of catalase and coagulase . confirmed growth of S. aureus. Methicillin resistance was determined by disk diffusion method according to CLSI guidelines. S.aureus with inhibition zone more than 18 mm were taken as methicillin-sensitive and those inhibition zone of less than 18 mm were taken as methicillin-resistant. Adequate information regarding identification of patient, clinical diagnosis, duration of hospital stay and clinical outcome were entered . Aftertaking consent from parents.Lab results were entered in the proforma. Children of all age groups up to 12 years of age and both sexes were included to avoid any bias. All patients clinically diagnosed to be suffering from staphylococcal infection (septicemia, pneumonia, skeletal infection, skin & soft tissue infection, meningitis ) who were admitted in pediatric ward were included. Results: Sixty patients with S. aureus infection were included in the study. Thirty patients were of MRSA and 30 were of MSSA. In MRSA group 12 (40%) patients remained in the hospital for less than a week and 18 (60%) patients stayed for more than a week but less than 3 weeks. In MSSA group 23(76.6%) patients were hospitalized for less than one week duration and 7(23.4%) patients were admitted for more than 1 week but less than 3 weeks duration. In MRSA group, 15(50%) patients recovered, 4(13.4%) patients improved, 2(6.6%) patients didn’t improved and 9(30%) patients expired. In MSSA group, 22(73.4%) patients recovered completely, 4(13.4%) patients improved, 2(6.6%) patients didn’t improved and 2(6.6%) patients expired. Conclusion: Children suffering from MRSA infection have more severe illness as compared to those suffering from MSSA infection. Duration of hospitalization of children suffering from MRSA infection is prolonged as compared to MSSA infection while clinical outcome is better in children suffering from MSSA infection as compared to MRSA infection.